RELATIONSHIP BETWEEN PERFORMANCE AND JOB SATISFACTION OF NURSES IN THE CENTRAL SURGICAL INSTALLATION OF DR. SAIFUL ANWAR HOSPITAL, EAST JAVA PROVINCE - Veny Ari Ristanti; Achmad Dafir Firdaus; Sismala Harningtyas (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: The quality of service in hospitals is related to the quality of health workers' performance. Several factors related to the implementation of the duties and responsibilities of nurses are greatly influenced by the ability of nurses to carry out their duties. The purpose of this study was to determine the relationship between performance and nurse job satisfaction.. Methods: The design of this study was observational analytic with a cross-sectional approach, using a total sampling technique with a sample of 50 respondents. The research instrument used a questionnaire sheet to measure performance and job satisfaction. Data analysis with the Somers'd correlation test with SPSS IBM Version 23 Results: The results of the Somers'd statistical test obtained a p value = 0.001, which can be concluded that there is a significant relationship between performance and nurse job satisfaction in the Central Surgical Installation of Dr. Saiful Anwar Hospital, East Java Province. Conclusions: Job satisfaction is a fairly interesting and important problem, because it is of great benefit to the interests of individuals, hospitals and society. For hospitals, research on job satisfaction is carried out in order to improve the quality of nursing care.